2005
DOI: 10.1002/em.20143
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies of the genotoxicity of ionizing radiation in human G0 T lymphocytes

Abstract: In an effort to mimic human in vivo exposures to ionizing irradiation, G(0) phase T lymphocytes from human peripheral blood samples were utilized for in vitro studies of the genotoxic effects of (137)Cs low-LET irradiation and (222)Rn high-LET irradiation. Both types of radiation induced mutations in the HPRT gene in a dose-dependent manner, with a mutant frequency (MF) = 4.28 + 1.34x + 7.51x(2) for (137)Cs (R(2) = 0.95) and MF = 4.81 + 0.67x for (222)Rn (R(2) = 0.51). Post (137)Cs irradiation incubation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In contrast, complex breaks include fragmented sugar damaged or missing bases in the vicinity of the break [64],[65]. While simple DSBs generated by endonucleases mainly cause small deletions, it is clear that a subset of random breaks leads to large deletions and translocations [43], [66][68]. For example, ionizing radiation induced hprt mutants resulted in deletions up to 56 kb whereas improper IgH class switching and spontaneous DSBs can lead to translocations [43], [66][68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, complex breaks include fragmented sugar damaged or missing bases in the vicinity of the break [64],[65]. While simple DSBs generated by endonucleases mainly cause small deletions, it is clear that a subset of random breaks leads to large deletions and translocations [43], [66][68]. For example, ionizing radiation induced hprt mutants resulted in deletions up to 56 kb whereas improper IgH class switching and spontaneous DSBs can lead to translocations [43], [66][68].…”
Section: Discussionmentioning
confidence: 99%
“…While simple DSBs generated by endonucleases mainly cause small deletions, it is clear that a subset of random breaks leads to large deletions and translocations [43], [66][68]. For example, ionizing radiation induced hprt mutants resulted in deletions up to 56 kb whereas improper IgH class switching and spontaneous DSBs can lead to translocations [43], [66][68]. Molecular characterization of large deletions and translocations revealed that they are mainly caused by microhomology-mediated repair [8],[43],[67],[69].…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis of CHO-K1 cells, following up from the study conducted by Hsie et al [117], failed to detect a difference between Hprt mutation spectra [118] and again in a similar contrast to some previous studies, work in human T lymphocytes [119] demonstrated less than 2% total gene deletions at the HPRT locus after exposure to radon and its daughters, although partial deletions were still present. Furthermore, human T lymphocytes exposed to high-LET radon (using the same methodology as described by Jostes et al [111]) and low-LET Caesium-137 found that the main marker of low-LET exposed lymphocytes were large deletions of the entire HPRT gene and high-LET exposure predominantly resulted in partial deletions and multiple single base changes [120]. Although not comparing high and low-LET exposures, other work in CHO cells using varying doses of Caesium-137 gamma-radiation has observed dose-dependent changes in mutation spectra [121] and a difference in mutation type between exposures of low (resulting mainly in point mutations) and high-dose (resulting in multibase deletion mutations).…”
Section: Genetic Effectsmentioning
confidence: 99%